Comprehensive performance measurement systems, mental model development, organizational justice, and employee performance: A study in Sharia Banks - Nurkholis Nurkholis; Ninda Ayu Wiranti (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2019)
This study aims to examine the effect of implementing a comprehensive performance measurement system to the development of mental models, organizational justice, and employee performance. Using survey with convenience sampling method, 63 data were collected. Respondents in this study are employees of sharia banks in Malang and Surabaya. Data analysis was run using Structural Equation Model (SEM) with SmartPLS application. The results show that comprehensive performance measurement system has a positive effect on the development of mental model and organizational justice. Besides, organizational justice has a positive effect on employee performance and mediates the effect of comprehensive performance measurement system on employee performance. On other hand, the development of mental model has no positive effect on employee performance. Thus, the implementation of a comprehensive performance measurement system and organizational justice in companies, especially sharia banks, can support the improvement in the employee performance.